Choir Singing as a Cross-cutting Focal Point of Knowledge, Attitudes and Values: A Proposal aimed at Students on the Degree in Early Childhood Education and Primary Education - Llorenç Gelabert Gual (Foro de Educación)
Singing in a choir comprises a number of specific musical aspects including the technical part of the singing voice; vocal ensemble; harmonies; aesthetics and musical taste. In practice, however, there are many cross-cutting elements that are not specifically musical but do play an important role in a choir. The preparation and development period for a concert is, in essence, a process of collective growth, where each component becomes an important foundation to enhancing the ensemble performance, and to a greater or lesser extent, offers a wide range of parameters in which to work. This procedure is a recurrent theme in early childhood education and primary teaching, but appears to occur less frequently during the training of music teachers or in higher-grade musical education. In this vein, a group of undergraduate students on the Degree in Early Childhood Education and Primary Education at the University of the Balearic Islands participated voluntarily in a collective singing trial. In consequence, they came to recognise the special psychosocial and attitudinal value of the experience. The opinions in this article are based on existing documents and relevant studies regarding the importance of collective singing. In the process, we also set out the experiment carried out at the University of the Balearic Islands.